Enhanced hydrogen storage capacity and reversibility of LiBH4 nanoconfined in the densified zeolite-templated carbon with high mechanical stability. (July 2015) - Shao, Jie; Xiao, Xuezhang; Fan, Xiulin; Huang, Xu; Zhai, Bing; Li, Shouquan; Ge, Hongwei; Wang, Qidong; Chen, Lixin
Abstract: Nanoconfining hydrogen storage material inside nanopores has emerged as an intriguing strategy to influence the material characteristics but also sacrifices part of system gravimetric and volumetric hydrogen capacity. Herein, we tackle these two challenges by nanoconfining LiBH4 into a new scaffold, zeolite-templated carbon (ZTC), with high porosity and excellent mechanical stability to form a densified nanoconfinement system. After nanoconfinement of LiBH4 and 750 MPa densification, the nanocomposite begins to release hydrogen at 194 °C, 181 °C lower than that of the bulk LiBH4 . The rehydrogenation of LiBH4 achieves under mild conditions with improved cycle stability. Moreover, the activation energy of hydrogen desorption is dramatically reduced by 60.4 kJ mol −1, coupled with the foaming effect of desorption almost eliminated. More importantly, the over-infiltrated LiBH4 @ZTC systems are capable of maintaining their good hydrogen storage performances, which is attributed to the interface/surface effect between hydrides and scaffolds. With ultra-high pressure densification and high uploading amount of LiBH4, the nanoconfined composite achieves an exceptional gravimetric capacity of 6.92 wt% and volumetric capacity of 75.43 g L −1 . These findings add new insights in the development of nanoconfinement systems with enhanced hydrogen storage capacity. Graphical abstract: Highlights: We firstly introduce a new scaffold with high mechanical stability in confined system. Dehydrogenation temperature of densified composite is significantly reduced by 181 °C. Rehydrogenation of LiBH4 achieves under mild condition with improved cycle stability. Catalysis arises from the interface/surface effect between hydrides and scaffolds. Succeeded in increasing the gravimetric and volumetric capacity of the confined system.